Nova contribuição ao conhecimento do gênero Diospyros Dalech. (Ebenaceae) no Brasil. - (:unkn) unknown (Museu Paraense Emílio Goeldi, 1963)
The present paper is a resume of the description of the species of the genus Diospyros in Brazil, with exclusion of the Amazonian species, that were reported in another work. In the material studied two new species are recognized, which are here described: D. duartei and D. araripensis. This study was based in the material from the herbaria NY, US, P, F, RB, R, MG and IAN.
Keywords: Diospyros Dalech.; Ebenaceae; Taxonomia vegetal; Plant taxonomy